INTRUDER DETECTION SYSTEM - Tan, Jia Chwen (Universiti Malaysia Sarawak (UNIMAS), 2020)
Nowadays, house security is a concern for everyone when they are out of their house. Anything important could be missing as there might have break-in happening in their house. Thus, house owner installs security camera in their house to monitor their house surrounding even though they are out from their house. To make the notification by security camera more meaningful, Intruder Detection System is being proposed. This system is powered by raspberry pi model 3B+ with camera module. The camera module in the raspberry pi model 3B+ will detect the objects and send them for the raspberry pi to process. Then it will compare the face data captured by the camera module with the data stored inside the database. If the person is determined to be unknown by the raspberry pi, it will attempt to analyse whether the person is doing any suspicious activity. If the raspberry pi determines the unknown person is doing suspicious activity, it will send notification to the mobile app to alert the house owner and recording video simultaneously. By using this system, house owners will be less concerned about their house.